Epiplakin expression is lost in psoriatic skin lesions and is downregulated by IFN-γ in ex vivo skin cultures - Kühtreiber, Hannes; Drexler, Corinne; Salek, Melanie; Auer, Lisa; Griss, Johannes; Mildner, Michael; Fuchs, Peter (Frontiers in Cell and Developmental Biology, 2025)
Proteins of the plakin family are predominantly expressed in the epidermis and play a crucial role in cytoskeletal assembly by crosslinking intracellular structural components with cell–cell junctions and the plasma membrane. While most plakins are critical for maintaining epidermal integrity, the role of epiplakin (EPPK1) in inflammatory skin disorders has not been thoroughly investigated. We therefore used single-cell RNA sequencing (scRNAseq) analysis, immunofluorescence, and ex vivo cytokine treatment of human skin explants to investigate EPPK1 regulation in psoriasis. ScRNAseq analysis of psoriatic and healthy skin revealed that EPPK1 was the only member of the plakin family showing specific downregulation in the epidermis of psoriatic lesions. This finding was corroborated at the protein level by immunostaining of human psoriasis samples showing a specific downregulation of EPPK1 in the suprabasal granular layer of psoriatic epidermis. Transcriptomic profiling of Eppk1−/− murine epidermis revealed reduced expression of genes involved in epithelial adhesion and lipid metabolism, partially overlapping with the psoriatic keratinocyte signature, suggesting that EPPK1 loss may predispose the skin to barrier dysfunction under inflammatory stress. Investigation of the mechanism underlying the EPPK1 regulation in psoriasis revealed that interferon-γ (IFN-γ) was the main cytokine involved in its downregulation in human ex vivo skin. Collectively, our findings demonstrate a specific IFN-γ-dependent downregulation of EPPK1 in psoriasis, suggesting that lack of EPPK1 might contribute to the epithelial defects observed in this inflammatory skin condition.